The Empowerment of Community Potential in Cirawamekar Village, Cipatat District, West Bandung Regency (A Case Study of Wayang Golek Craftsmen) - Yayat Rukayat; Solahuddin Ismail; Siti Nuraeni (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
One of the functions of government is to empower the community to achieve equity and accelerate welfare. For this reason, the government has formed government units down to the village level so that the empowerment process can run well and on target. Cirawamekar is a village in West Bandung Regency that has the potential for wood crafting in the form of Wayang Golek and souvenirs. Unfortunately, amid increasing appreciation coming from the international community, this does not have an impact on the welfare of the artisans in Cirawamekar Village. For this reason, this research was conducted to see the empowerment efforts carried out by the village government for the craftsmen. Through a descriptive qualitative method with a case study approach, this study found that the empowerment efforts carried out by the Cirawamekar Village government for the craftsmen were not optimal. The basic needs of the craftsmen, specifically promotion and marketing, have not been able to be carried out by the Cirawamekar Village government.